The Influence of Duties and Education Experience on New Personnel Duties in the Indonesian National Army's Operating Staff Environment - Azis Hakim (Universitas Pendidikan Ganesha, 2023)
New personnel in the TNI operations staff environment are expected to have sufficient skills and knowledge to be able to complete the assigned tasks. However, several factors such as complex tasks and lack of educational experience can affect the ability of new personnel to carry out these tasks. The purpose of this study is to determine the effect of task experience and education partially and simultaneously on the adaptation of new personnel assignments in the TNI Operations Staff Environment. The research method uses a survey with a quantitative approach. The sampling technique uses Simple Random Sampling. The sample size was 44 respondents. The results showed that a) task experience had a positive and significant effect on the adaptation of new personnel assignments; b) Task experience and education together have a positive and significant effect on the adaptation of new personnel assignments. It is recommended that in the selection of new personnel within the Indonesian Army Operations Staff, those who already have duty experience and education will support each other to facilitate the process of adjusting their duties. Looking at the dynamics of tasks in the TNI Operations Staff environment, it is recommended that task experience with the priority of work mastery and education with the priority of developing science and technology is the most ideal combination for accelerating adaptation. processes within the TNI Operations Staff so that they can subsequently smoothly carry out their duties within the TNI Operations Staff.